2019
DOI: 10.3390/app9204466
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Coastal Zone Data of Northern Yantai Collected by Remote Sensing from 1990 to 2018

Abstract: Using remote sensing images of different time phases from 1990 to 2018, the surface coverage information of northern Yantai (coastline, 2 km from coastline to land) was extracted by means of average high tide line and visual interpretation. The end point change rate (EPR) and linear regression rate were used to study the coastline change rate, the fractal dimension of the coastline in the study area was analyzed, and the change of the type of coastal surface cover was analyzed by the transition matrix. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
2
5
0
1
Order By: Relevance
“…Overall, the correlation analysis revealed that groundwater chemical characteristics were mainly related to rock weathering and anthropogenic activities. In addition, the effect of saline water interactions contributed significantly to the increase in the hydrochemical parameters contents of the coastal QA, which is consistent with previous studies carried out in the same study area [15,18,41]. On the other hand, HCO 3 − showed moderate positive correlations with Ca 2+ and Mg 2+ in both aquifers, while SO 4 2− revealed a moderate to good positive correlation with Ca 2+ , suggesting carbonates and sulfate minerals dissolutions.…”
Section: Correlation Relationshipsupporting
confidence: 90%
“…Overall, the correlation analysis revealed that groundwater chemical characteristics were mainly related to rock weathering and anthropogenic activities. In addition, the effect of saline water interactions contributed significantly to the increase in the hydrochemical parameters contents of the coastal QA, which is consistent with previous studies carried out in the same study area [15,18,41]. On the other hand, HCO 3 − showed moderate positive correlations with Ca 2+ and Mg 2+ in both aquifers, while SO 4 2− revealed a moderate to good positive correlation with Ca 2+ , suggesting carbonates and sulfate minerals dissolutions.…”
Section: Correlation Relationshipsupporting
confidence: 90%
“…Garis pantai dalam kajian ini adalah garis air pada saat perekaman citra satelit (Sui et al, 2020). Esmail et al (2019) melakukan perbandingan tiga metode ekstraksi garis pantai, yaitu squared error clustering method (SECM), penggunaan nilai ambang batas dan digitasi, dan menyimpulkan metode SECM adalah metode terbaik, tetapi metode tradisional melalui interpretasi visual manusia dan interaksi komputer masih umum digunakan para ahli untuk mendeliniasi garis pantai (Zhou et al, 2019). Oleh karena itu kajian ini mengadopsi metode tersebut.…”
Section: Deliniasi Garis Pantaiunclassified
“…e method of coastline interpretation includes visual interpretation and automated remote sensing image interpretation [51]. Methods of automatic analysis, such as the edge detection algorithm, the mathematical morphology algorithm, the region-growing algorithm, the data mining method, and the neural network method proposed in recent years, are widely used around the world, but conventional methods, such as the visual interpretation of human-computer interaction, are still widely used by experts to extract coastal information [52]. e method of human-computer integrated visual perception was therefore adopted in this article.…”
Section: Extraction and Classification Of Qingdao Coastlinementioning
confidence: 99%